A Review on Extraction, Characterization, and Applications of Bioactive Peptides From Pressed Black Cumin Seed Cake - Zaky, Ahmed A.; Shim, Jae-Han; Abd El-Aty, A. M. (Frontiers in Nutrition, 2021)
Plenty of black cumin cake was generated as a natural waste material after pressing the oil. Nigella sativa (black cumin) seeds and cakes are of precious nutritional value as they contain proteins, phenolics, essential amino acids, and bioactive compounds. Owing to their antioxidant properties, scientists and food manufacturers have extensively developed them. Notably, global awareness among consumers about the benefits of innovative food ingredients has been increased. Meanwhile, it has to be noted that vast amounts of cake by-products are not effectively utilized, which might cause economic loss and environmental consequences. This review aimed to highlight the antioxidant abilities, extraction, characterization, functional characteristics, and utilization of active peptides acquired from black seed oil cake. This overview would critically evaluate black seed cake proteins, plentiful in bioactive peptides that might be utilized as valuable additives in feed, food, pharmaceutical, and cosmetic industries. The addition of bioactive peptides to restrain the oxidation of fat-based products and preserve food safety is also addressed.